2021
DOI: 10.1186/s12913-021-06523-z
|View full text |Cite
|
Sign up to set email alerts
|

Organisational and advance care planning program characteristics associated with advance care directive completion: a prospective multicentre cross-sectional audit among health and residential aged care services caring for older Australians

Abstract: Background Advance care planning (ACP) and advance care directive (ACD) completion improve outcomes for patients, family, clinicians and the healthcare system. However, uptake remains low. Despite increasing literature regarding organisational-level ACP characteristics leading to success, there is a lack of data measuring the impact of these factors on ACD prevalence. Methods A prospective multi-centre, cross-sectional audit of health records among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Supporting this to occur in practice is a challenge, as good quality patient-clinician communication can take time and increase staff workloads. However, the fact that this remains a strong theme in the literature points towards the need for strategies to further build this capacity into the role of clinicians by remunerating additional time [ 45 , 46 ] to optimise the provision of quality EOL care.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this to occur in practice is a challenge, as good quality patient-clinician communication can take time and increase staff workloads. However, the fact that this remains a strong theme in the literature points towards the need for strategies to further build this capacity into the role of clinicians by remunerating additional time [ 45 , 46 ] to optimise the provision of quality EOL care.…”
Section: Discussionmentioning
confidence: 99%
“…Initiation of ACP conversations seems to be a major barrier, as patients may be reluctant to broach the subject with their health care providers, while clinicians report having insufficient training or time to conduct ACP discussions [ 22 30 31 ] during busy clinic visits. Though patients believe that their medical providers should initiate conversations about ACP [ 32 33 ], 17% or fewer of patients report discussing ACP with their medical team [ 34 ]. Given the barriers for many patients in learning about and completing ACP, it is important to explore alternative approaches that may better support health care providers in facilitating this vital service [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…From a patient perspective, even fewer patients report having had ACP conversations with their nurses. Studies of Canadian (Heyland et al, 2013) and Australian (Detering et al, 2021) patients indicate that only 5.8% to 8% recall having had an ACP discussion with their registered nurse. The discrepancy between these numbers may be related to over-reporting by nurses and/or under-reporting by patients.…”
Section: Introductionmentioning
confidence: 99%
“…These studies found that nurses typically spend only ¼ of their shift in direct patient care with their patients, resulting in little time for engaging in ACP (Allen, 2014(Allen, , 2015Hobgood et al, 2005). From an institutional standpoint, most acute care organizations lack policies and procedures related to who should engage in ACP with patients, when it should take place, and if it is essential in the care of patients (Baughman et al, 2015;Detering et al, 2021;Martina et al, 2021;Mohan et al, 2020;Rietze et al, 2018). Consequently, nurses are not clear whether ACP is a part of their scope of practice in acute care settings (Putman-Casdorph et al, 2009;Rietze et al, 2018;Vanderhaeghen et al, 2018) since they receive limited direction, education, training, and templates on how to engage patients in ACP (Baughman et al, 2015;Martina et al, 2021;Whitehead et al, 2021), and are uncertain how, or if, ACP influences treatment planning in their organization (Duke & Thompson, 2007;Putman-Casdorph et al, 2009).…”
Section: Introductionmentioning
confidence: 99%